2014
DOI: 10.1039/c4ra00934g
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of a silver nanoparticle–graphene oxide composite and its application for As(iii) detection

Abstract: We report a facile and green synthetic approach to synthesize a silver nanoparticle (AgNPs)–graphene oxide (GO) composite using beta cyclodextrin as a stabilizing agent and ascorbic acid as a reducing agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(36 citation statements)
references
References 51 publications
2
34
0
Order By: Relevance
“…A wide linear response to 4‐NP in the ranges of 1.0 × 10 −8 to 1.0 × 10 −7 m and 1.0 × 10 −7 to 1.5 × 10 −3 m was achieved with a low detection limit of 8.9 × 10 −10 m . Furthermore, Dar et al reported the application of AgNPs‐GO modified glassy carbon electrode (AgNPs‐GO/GCE) for arsenic(III) detection, which exhibited a wide linear range ((13.33–375.19) × 10 −9 m ) and a high sensitivity (180.5 µA µ m −1 ) with a detection limit of 0.24 × 10 −9 m . Shaikh et al constructed Ag–rGO as nitrite (NO 2 − ) sensor and found that this sensor exhibited two linear ranges: one from 10 × 10 −9 to 1000 × 10 −9 m with a sensitivity of 3.0 × 10 4 µA m m −1 cm −2 ( R = 0.999) and another from 10 × 10 −6 to 1000 × 10 −6 m with a sensitivity of 373.46 µA m m −1 cm −2 ( R = 0.978), with a sensitive detection below 1 ppm .…”
Section: Sensorsmentioning
confidence: 99%
“…A wide linear response to 4‐NP in the ranges of 1.0 × 10 −8 to 1.0 × 10 −7 m and 1.0 × 10 −7 to 1.5 × 10 −3 m was achieved with a low detection limit of 8.9 × 10 −10 m . Furthermore, Dar et al reported the application of AgNPs‐GO modified glassy carbon electrode (AgNPs‐GO/GCE) for arsenic(III) detection, which exhibited a wide linear range ((13.33–375.19) × 10 −9 m ) and a high sensitivity (180.5 µA µ m −1 ) with a detection limit of 0.24 × 10 −9 m . Shaikh et al constructed Ag–rGO as nitrite (NO 2 − ) sensor and found that this sensor exhibited two linear ranges: one from 10 × 10 −9 to 1000 × 10 −9 m with a sensitivity of 3.0 × 10 4 µA m m −1 cm −2 ( R = 0.999) and another from 10 × 10 −6 to 1000 × 10 −6 m with a sensitivity of 373.46 µA m m −1 cm −2 ( R = 0.978), with a sensitive detection below 1 ppm .…”
Section: Sensorsmentioning
confidence: 99%
“…70 Fig. 107 Some of other developed electrochemical sensors for the detection and determination of heavy metal ions such as Hg(II), [108][109][110][111] Cr(VI), 69,109 Pb(II), 113,114 Cd(II), 114,115 As(III) [116][117][118] and Cu(II) 119 using the nanostructured materials are listed in Table 1. The Au NPs ($10 nm in diameter) were well dispersed on the as-prepared TiO 2 NTs.…”
Section: Detection Of Heavy Metalsmentioning
confidence: 99%
“…Among them, Ag is a noble metal that possesses high electrical conductivity, remarkable antibacterial activity, and excellent catalytic activity. Dar et al 28 proposed a low-cost facile method to fabricate an Ag NP-reduced graphene oxide (AgNP/rGO) composite to form an electrochemical sensor that showed high sensitivity for an environmentally toxic metal element, As. Moreover, a heminfunctionalized graphene oxide was fabricated to simultaneously determine AA, DA and UA.…”
Section: Introductionmentioning
confidence: 99%